Clinicopathological findings, treatment response and predictors of long-term outcome in a cohort of lupus nephritis patients managed according to the Euro-lupus regime: a retrospective analysis in Sri Lanka. (December 2017) - Herath, Nalaka; Ratnatunga, Neelakanthi; Weerakoon, Kosala; Wazil, Abdul; Nanayakkara, Nishantha
Abstract Background Despite the improvement in survival of patients with lupus nephritis (LN) globally, there is sparse data from Sri Lanka (SL). The current study aims to describe the clinicopathological findings, treatment response and predictors of long-term outcome of patients with WHO class III–IV LN in SL, managed according to the Euro-lupus regime. Results Of 72 patients, 64 were females. In half of them, LN was diagnosed within the 1st year of the illness. The most common presenting feature was sub-nephrotic proteinuria. Sixteen and twenty patients had nephrotic syndrome and abnormal renal function respectively at the time of diagnosis. Fifty-four patients (75%) responded to the Euro-lupus regimen [CR, 20 (28%); PR, 34(47%)]. Later at 6 months, 65 patients (90%) achieved remission [CR, 31(43%); PR, 34 (47%)]. Seven patients experienced treatment failure. During the total duration of follow up, 54 patients remained in complete or partial remission, 26 developed renal relapses, and 19 suffered severe infective episodes. Renal relapses were more common in people who achieved partial remission than complete remission. The long term renal outcome was not associated with age, sex, severity of proteinuria, class of LN or initial renal function. Patients who achieved remission at 6 months had a good long-term outcome. Conclusions The demographic and clinical features of WHO class III and IV LN in Sri Lankan patients were similar to that reported in the global literature. 75% of patients responded to the Euro-lupus regimen. Therefore, this regime is a suitable initial regimen for LN patients in SL. Good long-term renal outcome can be predicted by early response to therapy. Further studies are necessary to explore better treatment options for patients who fail to achieve remission during initial therapy.